Orbital Apex Syndrome: A Case Series in a Tertiary Medical Center in Southern Taiwan - Lee, Peng-Hsuan; Shao, Shih-Chieh; Lee, Wan-Ju Annabelle (Frontiers in Medicine, 2022)
Background The etiologies of orbital apex syndrome (OAS) are infection, inflammation, trauma, neoplasms, and vascularity. There have no reports about OAS in Taiwan up to date. This study aimed to present ophthalmic clinical features, determine the causes and evaluate the visual prognosis of orbital apex syndrome (OAS) patients in Taiwan. Methods This was a retrospective review from electronic records in National Cheng Kung University Hospital between January 1, 2017 and December 31, 2019. Patients diagnosed with OAS were recruited to review the ocular symptoms and signs, visual acuity, related images, contributing causes for OAS, treatment and visual prognosis. Results Twenty cases (mean age: 65.55±13.06; male: 75%) with the diagnosis of OAS were included in this study. All patients presented as unilateral involvement, but the initial ocular presentations and etiologies varied. For example, blurred vision was reported in 80% of these patients, and tumor-related compression (55%) and infection (15%) were the most frequent causes for the OAS. After the follow-up, we found 35% of patients’ visions declined or worsen to the blindness, 15% of patients’ visions remained stable, 20% of patients’ visions had mild improvement, and 35% of patients’ visions were not measured because of debilitating clinical condition. We identified 3 OAS patients with mortality (15%), and all of them were attributed to the underlying malignancies. Conclusion The clinical magnifications and etiologies of OAS are heterogamous in Taiwan. Our findings indicated the tumor-related compression is the most frequent causes of OAS in Taiwan, and it is also related to poor clinical outcomes.